Neurophysiological follow-up of two siblings with Crigler-Najjar syndrome type I and review of literature - Bayram, Erhan; Öztürk, Yeşim; Hız, Semra; Topçu, Yasemin; Kılıç, Murat; Zeytunlu, Murat (The Turkish Journal of Pediatrics, 2013)
Crigler-Najjar syndrome type I is an autosomal recessive inherited disease and rarely seen in childhood. Bilirubin neurotoxicity is the morbidity of the disease due to the elevated unconjugated bilirubin levels. Mental retardation, seizures, cognitive dysfunction, oculomotor nerve palsy, ataxia, choreoathetosis, and spasticity may be seen. Due to the high bilirubin levels, alterations in the neurophysiological studies may be detected. In this study, we describe two siblings who were diagnosed with Crigler-Najjar syndrome type I who underwent a successful liver transplantation using a single cadaveric organ, together with their neurophysiological follow-up and review of the literature.